Computational reflection in software process modeling: The SLANG approach - Bandinelli, S.; Fuggetta, A. (Proceedings of 1993 15th International Conference on Software Engineering, 1993)
SLANG is a domain-specific language for software process modeling and enactment. The authors present the basic features provided by SLANG to support the enactment and, in particular, dynamic evolution of a process model. Software production processes are subject to changes during their lifetime. Therefore, software process formalism must include mechanisms to support the analysis and dynamic modification of process models, even while they are being enacted. It is thus necessary for a process model to have the ability to reason about its own structure. Petri net based process languages have been criticized because of the lack of these reflective features and their inability to effectively support process evolution. The reflective features offered by SLANG are outlined, which is a process formalism based on a high-level Petri net notation. In particular, the mechanisms are discussed to create and modify different net fragments while the modeled process is being enacted.< >